TINJAUAN HUKUM ISLAM TERHADAP PRAKTIK JUAL BELI TANAH DI DESA KARANGDORO KECAMATAN TEGALSARI KABUPATEN BANYUWANGI - Muhammad Ala’uddin; Mukhtar Syafaat (Jurnal Ekonomi Syariah Darussalam, 2020)
This study aims to determine the practice and review of Islamic law related to the sale and purchase of land in Karangdoro Village, Tegalsari District, Banyuwangi Regency and to find out. The results obtained from research on the practice of buying and selling land in Karangdoro Village. In buying and selling through a broker, a broker gets 5% of the proceeds from the sale, which percentage has become a local custom or taken from the additional selling price of the land. In addition, it is usually when a land owner asks for the net price of the land sale. After knowing the price asked by the land owner, the realtor will find a buyer and offer the goods. After the broker makes a price agreement with the buyer, the buyer will be brought together with the land owner to make an agreement or agreement. The sale and purchase transaction of land in Karangdoro Village is legal according to the review of Islamic law, because it is in accordance with the terms and conditions of sale and purchase, and the increase in prices made by brokers in selling land is permitted under Islamic law because it has received permission from the land owner.